PREVALENCE OF EXERTIONAL ASTHMA AND ITS ASSOCIATION WITH FITNESS LEVEL IN PLAYERS (The Research of Medical Science Review, 2025)
Exertional asthma is a condition in which the airways become narrow or squeeze by the performance of hard physical activity. Sign and symptoms of exertional asthma include shortness of breath, wheezing, coughing, chest tightness, fatigue. Shortness of breath or wheezing get worse that make it hard to breathe. Air that is breathing in from mouth is dryer and cooler than breathe through nose. The complications that can be appearing due to exertional asthma are severe breathing difficulties, bronchoconstriction, and inability to exercise which effects quality of life. The factors that trigger exertional asthma are dry air Cold air Activities with long periods of deep breathing, such as long-distance running, swimming, polluted air. We will perform the cross-sectional study to check prevalence of exertional asthma in athletes. Moderate exercise has been shown to be beneficial for people with asthma, but repetitive, high-intensity exercise can contribute to the development of exertional asthma. OBJECTIVE: The major aim of the study was to check the prevalence of exertional asthma and its relationship with fitness and how BMI affects the exertional asthma in players. METHODOLODY: A cross sectional study design with the sample size of 80 was used to collect data from different universities in Faisalabad. Convenient non-probability sampling technique was used recruit subjects in selection of study sample after screening with inclusion and exclusion criteria. After that we take that participant which was meeting our inclusion criteria. We collected data by using self-made screening sheet. After collecting data, statistical analysis was done through SPSS version 20. RESULTS: The data was analyzed through SPSS version 20. The mean age of participants is 23 years. The prevalence of exertional asthma in male was 63.9% and 36.1% in female. According to our sample size 11.1% have moderate, 25% have somewhat severe, 41.7% severe and 5.6% very severe exertional asthma. This research also aims that exertional asthma has significance influence on BMI and a great association with fitness. CONCLUSION: This research concludes that exertional asthma is most commonly present in the age of 23. The prevalence of exertional asthma is more in male rather than female. Our research also concludes that exertional asthma has a great association with fitness level and BMI of players.